2023
DOI: 10.1177/09603271231158047
|View full text |Cite
|
Sign up to set email alerts
|

MAPK-interacting kinases inhibition by eFT508 overcomes chemoresistance in preclinical model of osteosarcoma

Abstract: The MAPK-interacting kinases 1 and 2 (MNK1/2) have generated increasing interest as therapeutic targets for many cancers with little known in osteosarcoma. This study evaluated the efficacy of eFT508, a highly selective inhibitor of MNK1/2, as single drug alone and in combination with paclitaxel in preclinical models of osteosarcoma. EFT508 is active against multiple osteosarcoma cell lines via inhibiting growth, survival and migration. It also demonstrates anti-osteosarcoma selectivity with much less toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Our results showed that eFT508, a potent inhibitor of MNK1 and MNK2 with IC50 values in the low nanomolar range [21], does not cause general toxicity in mice at an effective dose. The anti-cancer activities of eFT508 have recently been revealed in osteosarcoma, leukemia, glioblastoma, and breast cancer, particularly its ability to overcome chemoresistance [22][23][24][25]. eFT508 has entered clinical trials for solid cancers, leukemia, and lymphoma (ClinicalTrials.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that eFT508, a potent inhibitor of MNK1 and MNK2 with IC50 values in the low nanomolar range [21], does not cause general toxicity in mice at an effective dose. The anti-cancer activities of eFT508 have recently been revealed in osteosarcoma, leukemia, glioblastoma, and breast cancer, particularly its ability to overcome chemoresistance [22][23][24][25]. eFT508 has entered clinical trials for solid cancers, leukemia, and lymphoma (ClinicalTrials.…”
Section: Discussionmentioning
confidence: 99%